Land use evaluation for Kuala Selangor, Malaysia using remote sensing and GIS technologies - Nedal A Mohammad,; Sharifah Mastura SA ,; Johari Mat Akhir, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
Land evaluation is the process of predicting the potential use of land on the basis of its attributes and is essential in identifying the best land management practice for sound land use planning. The key objective of this study is to evaluate landuse/cover in Kuala Selangor district, Selangor as the knowledge about land use and land cover has become increasingly important in Malaysia’s goal to overcome the problems of haphazard, uncontrolled development, deteriorating environmental quality, loss of prime agricultural lands, destruction of important wetlands, and loss of wildlife habitat. The study integrates remote sensing and GIS technologies for landuse/cover evaluation. In evaluating landuse for sustainable use of natural resources several maps were taken as parameters and obtained from digital classification of SPOT 2005 data by means of supervised modes with maximum likelihood algorithm using necessary ground truth data. The vegetation density using Normalized Differential Vegetation Index (NDVI) of Kuala Selangor was classified into five categories, namely, very high (775.51 km2), high (182.61km2), moderate (67.07 km2), low (77.44 km2), and non-vegetation areas (91.35 km2). Soil suitability map and subclasses were prepared to demonstrate how soil varied in behaviour or suitability for specialised purposes. Three soil types were identified including S2 (42%), S4 (45.63%) and S5 (12.37%). Overlay analyses of landuse and landcover with vegetation density, soil suitability and erosion risk were also presented. The actual distribution and area of the classes in all layers were analysed